Predictive Influence of Psychosocial Work Hazards on Work-Related Burnout and Organizational Deviance Among Primary School Teachers - Ede, Moses Onyemaechi; Mawila, Daphney (Program Studi Bimbingan dan Konseling Islam, 2025)
It is quite unfortunate that workers in developing countries experience job dissatisfaction accruing from hazardous work settings. These seemed to have posed mental and physiological stress on individuals, leading to unwholesome and unethical practices. Given these worrisome situations, this study investigated the relationship between psychosocial work hazards on work-related burnout and organizational deviance among primary school teachers. In pursuance of this aim, two research questions and hypotheses guided this study. A correlation design was employed in this study. A total of 254 primary school teachers participated in the study. Three scales that measured psychosocial work hazards, work-related burnout, and organizational deviance were used in assessing the participants. Pearson product-moment correlation and Linear regression statistics were used to analyze the research questions and hypotheses. The correlation analysis results revealed that psychosocial work hazards are associated with work-related burnout and organizational deviance among primary school teachers. Also, the results showed that psychosocial work hazards have a significant influence on work-related burnout and organizational deviance among primary school teachers. Practice implications for sustainable development were highlighted.